Análise proteômica diferencial revela que a ação anticâncer do WIN55,212-2, agonista canabinoide, é mediada pela inibição da via AKT/ mTOR - França, Jonas Costa de (2025)
Colorectal cancer (CRC) is the second most prevalent type of cancer in men and women in Brazil. The treatment of CRC still presents challenges, reinforcing the need for new therapeutic strategies. In this context, cannabinoids have demonstrated antitumor potential in preclinical studies, with emphasis on WIN 55,212-2, a non-selective agonist, which also presents neuroprotective potential in models of neuropathy induced by oxaliplatin, a first-line antineoplastic agent in the treatment of metastatic CRC. Considering the scarcity of studies on the effects and mechanisms of WIN 55,212-2 in a murine colorectal adenocarcinoma cell line (CT26.WT), the objective of this study was to identify key proteins involved in the antineoplastic effect of WIN 55,212-2 in a CT26.WT cell line through a shotgun proteomic approach. Initially, the cytotoxicity of WIN 55,212-2 was evaluated after 72 and 96 hours of treatment in the CT26.WT cell line. After determining its IC50, the protein extraction and digestion of cells treated and untreated with WIN 55,212-2 were performed for subsequent analysis by shotgun proteomics. Membrane integrity, ROS production, cell migration, the effect of the combination of WIN 55,212-2 with oxaliplatin and the effect on the AKT/mTOR pathway were also evaluated. WIN 55,212-2 obtained an IC50 of 6.69 μM and 5.4 μM at 72 and 96 hours of treatment. The total number of proteins identified was obtained and the gene ontology and the network of interactions between them were analyzed. A total of 1148 proteins were obtained, 332 of which were exclusive to the control group and 116 to the treated group, while 700 were in both groups. Of this total, 26 proteins were identified that are involved in biological processes such as protein processing and degradation, cytoskeleton reorganization, nucleotide metabolism and chemoresistance pathways. Analysis of the interactions between the proteins indicated alterations in relevant oncogenic signaling pathways, such as the PI3K/AKT/mTOR and NF-kB pathways. In addition, the inhibitory effect of WIN 55,212-2 on the AKT/mTOR pathway, a reduction in the migratory capacity of the treated cells, impairment of the integrity of the cell membrane and induction of oxidative stress were observed. Finally, the combination of WIN 55,212-2 with oxaliplatin showed greater potency when compared to oxaliplatin alone. It is concluded that WIN 55,212-2 has potential as an antitumor agent in CRC cell lines, evidencing its inhibitory effect on the AKT/mTOR pathway, its ability to modulate cellular processes critical for tumor progression and its ability to potentiate the cytotoxic effects of oxaliplatin. These results not only highlight the relevance of nonselective cannabinoid agonists as a therapeutic alternative, but also highlight the importance of future investigations to explore the clinical applications of these compounds in the management of CRC.